Four component meningococcal capsular Group B vaccine in preterm infants. - Sadarangani, M; Barlow, S; Anthony, M; Pollard, A (Oxford University Press, 2017)
The 4CMenB vaccine was introduced into the routine immunization schedule in the UK in September 2015 to protect against group B Neisseria meningitidis meningitis and septicemia. The vaccine is reactogenic in young infants, causing fever in 51-65% when co-administered with other vaccines [1, 2]. This led to the unprecedented recommendation that all infants receive prophylactic paracetcmol (acetaminophen) with the vaccine. Preterm infants are immunized at the same chronological age and same schedule as term infants but have higher rates of post-immunization adverse events (AEs), particularly those infants born at <28 weeks gestation who are hospitalized in the neonatal unit when immunized [3]. Preterm babies were excluded from 4CMenB trials pre-licensure and no such trials have been registered (clinicaltrials.gov, 14th October 2016). Administration of a reactogenic vaccine in this population has led to heightened concern about AEs. This may impact on use of the vaccine in very preterm infants until they are discharged home, thus delaying protection of this vulnerable group against meningococcal disease.